Analyzing the Environmental Impact of Livestock Manure Recycling Process Using Life Cycle Assessment - Hee Yeon Kang; Jae Young Lee; Geon Yong Kim; Yong Woo Hwang; Kwang Ho Park; Dong Jun Lee (대한환경공학회지)
Objectives This study aims to assess the environmental impact of the composting process, which constitutes 75.3% of the domestic livestock manure recycling methods, and to determine the environmental impacts of methane and nitrous oxide, the major greenhouse gases in the livestock sector, as well as ammonia, a precursor to fine particulate matter that has recently become a social issue. The analysis will focus on the categories of climate change and fine particulate matter formation to identify the most significant factors impacting the environment. Methods This study applied the Life Cycle Assessment (LCA) methodology according to ISO 14040/14044 standards to evaluate the environmental impact of producing one bag (20kg) of livestock manure compost. The system boundary included the transportation of livestock manure and sawdust to the composting facility and the compost production process. The methodology applied for impact assessment was the ReCiPe 2016 v.1.1 Midpoint (H) method, which allows for a more global evaluation by utilizing worldwide average data. Results and Discussion The impact assessment of livestock manure compost production revealed that producing one bag contributes 2.667 kg CO2-eq. to climate change, with electricity consumption responsible for 68.95% of emissions. Carbon dioxide (CO2) is the dominant greenhouse gas, making up 84.37% of the total. Particulate matter formation is 0.037 kg PM2.5-eq., with 91.97% resulting from emissions during the composting process. Ammonia (NH3) is the main cause of particulate matter, accounting for 92.02% of emissions. Conclusion Based on the research, electricity consumption is the main factor affecting climate change in compost production, and ammonia is the primary cause of fine particulate matter. This study provides a case for evaluating the environmental impact of livestock manure composting and can serve as a foundational reference for developing policies and technologies to address climate change and fine particulate matter issues.